Improving English Reading Skills Comprehension Through SQ4R Methode for Class X Senior High School In MAN 1 Mandailing Natal - Irma Sari; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
This study aims to obtain data on improving English reading comprehension skills through the SQ4R method for class X students. The research subjects were students in class X.in the second semester of the 2020/2021 academic year. This research was carried out using the Kemmis and Mc. Taggart carried out with the stages of planning, implementation, observation, and reflection. The results of the study using the SQ4R method showed that the data obtained from the evaluation test of reading comprehension of students who scored 75 in the first cycle was 55.55% and in the second cycle it was 83.33%. While the monitoring of teacher and student activities in the first cycle of the first meeting was 55% and the second meeting was 70%, while the second cycle of the first meeting was 85% and the second meeting was 90%. Thus, reading comprehension using the SQ4R method can improve students' reading comprehension skills in class X